The influence of climate change on brood size and breeding time in three tit species in Sweden, 1962–2019 - Ryttman, Hans (Ornis Svecica, 2024)
Climate change is expected to affect many biological systems, including the timing of seasonal events such as breeding in birds. In this study, I investigated how brood size and timing of reproduction (measured as median date for ringing of broods) changed for three tit species in Sweden 1962–2019 using data reported to the Swedish Bird Ringing Centre. The brood size for the Coal Tit Periparus ater increased from 7.74 between 1962–2001 to 7.98 young between 2002–2019, while no change was detected for Crested Tit Lophophanes cristatus or Willow Tit Poecile montanus. The largest biological effects were seen for timing of reproduction, with Coal Tits and the Crested Tits initiating breeding about seven days earlier at the end of the study period compared to the 1960s. The Willow Tit data also suggested earlier breeding, but only by about two days across the study period.